Odpowiedź :
Odpowiedź:
a)3x+4-x+2=4x-5+3x-4
2x-7x=-9-6
-5x=-15/:(-5)
x=3
spr.
3*3+4-3+2=4*3-5+3*3-4
9+4-3+2=12-5+9-4
12=12
L=P
b)2x-3+x+5+4x=3+3x-4+2x-5
7x-5x=-6-2
2x=-8/:(-2)
x=-4
spr.
2*(-4)-3+5+4*(-4)=3+3*(-4)-4+2*(-4)-5
-8-3+5-16=3-12-8-5
-22=-22
L=P
Szczegółowe wyjaśnienie:
Odpowiedź:
a)
3x+4 - x+2=4x - 5+3x - 4
3x - x - 4x - 3x= - 5 - 4 - 4 - 2
- 5x= - 15 /:( - 5)
x=3
spr
3*3+4 - 3+2=4*3 - 5+3*3 - 4
12=12
b)
2x - 3+x+5+4x=3+3x - 4+2x-5
2x+x+4x - 3x - 2x=3 - 4 - 5+3 - 5
2x= - 8 /:2
x= - 4
spr
2*( - 4) - 3 - 4+5+4*( - 4)=3+3*( - 4) - 4+2*( - 4) - 5
- 8 - 2 - 16=3 - 12 - 4 - 8 - 5
- 26= - 26
Szczegółowe wyjaśnienie: